(untitled) (Journal of Tikapur Multiple Campus, 2022)
This paper examines teachers’ perceptions of the academic and physical aspects of the English Textbook of Grade Ten. The researcher selected fifteen teachers from five schools using a judgmental non-random sampling method. The collected data and the teachers’ opinions were determined and analyzed by studying the book and evaluated using checklist tools. The main finding of this study shows that the textbook has both strong and weak points. Strong aspects of a textbook are an attractive cover page, biased free language, easily perceptible vocabulary, appropriate exercises, clearly reflected objectives, listening texts, and sufficient speaking and reading texts. The weaknesses are poor binding, poor paper quality, lack of skill focus on exercises, lack of illustrations, lack of references and supplementary materials as well as teacher’s guide. The results of this study could be helpful in the development of appropriate English textbooks of grade ten. Based on the finding, the paper also recommends improving the textbook.